PERAN MEDIASI RETURN ON EQUITY PADA PENGARUH DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI INDONESIA - Linzzy Pratami Putri; Irma Christiana Christiana; Riska Dwi Yana (Jurnal Ilmu Manajemen, 2022)
This study aims to determine the effect of the debt-to-equity ratio on stock prices through return on equity. The research approach used in this study is associative. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2019 period, totalling 65 companies. The sampling technique in this study was purposive sampling, so the sample in this study amounted to 42 property and real estate companies listed on the Indonesia Stock Exchange for the 2018-2019 period. The data analysis technique in this study uses path analysis, classical assumption test, t-test, and coefficient of determination test. The results indicate that the debt-to-equity ratio negatively and significantly affects stock prices. The debt-to-equity ratio has a positive and insignificant effect on return on equity. Return on equity has a positive and insignificant effect on stock prices. Partially, the debt-to-equity ratio to stock price through return on equity has a positive and insignificant effect, which means that return on equity does not mediate the relationship between debt-to-equity ratio to stock price.